2018
DOI: 10.1038/s41430-018-0304-x
|View full text |Cite
|
Sign up to set email alerts
|

Extra virgin olive oil: More than a healthy fat

Abstract: The beneficial effects of a Mediterranean diet on human health and, in particular, on lowering risk of cardiovascular disease, has been mainly attributed to its high content to extra virgin olive oil (EVOO). While its main fatty acid, oleic acid, is considered important to these effects, EVOO has other biological properties that depend on, or are potentiated by other minor components of this oil. Initially, the mechanisms considered as possible causes of this cardioprotective effect of EVOO were based on the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
157
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(163 citation statements)
references
References 109 publications
(119 reference statements)
4
157
0
2
Order By: Relevance
“…Several studies have indicated relationships between the saturation of dietary fat and the concentrations of total plasma cholesterol and higher blood pressure [5], hepatic steatosis [6], adipose chronic inflammation [6], ectopic lipid deposition in the liver and brown fat [6], overweight [6,7], hyperinsulinemia [7], and hepatic insulin resistance [8]. However, high fat diets that are rich in monounsaturated fatty acids exert a protective role [9][10][11][12][13][14][15].High monounsaturated fatty acids diets also have demonstrated an effect on the secretion of the insulinotropic peptide GLP-1 (glucagon-like peptide 1) [16,17]. GLP-1 is an incretin hormone with antidiabetic action that is capable of stimulating insulin secretion [18,19], increasing beta cell neogenesis [20], inhibiting beta cell apoptosis [20], inhibiting glucagon secretion [21], delaying gastric emptying, and inducing satiety [20,21].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated relationships between the saturation of dietary fat and the concentrations of total plasma cholesterol and higher blood pressure [5], hepatic steatosis [6], adipose chronic inflammation [6], ectopic lipid deposition in the liver and brown fat [6], overweight [6,7], hyperinsulinemia [7], and hepatic insulin resistance [8]. However, high fat diets that are rich in monounsaturated fatty acids exert a protective role [9][10][11][12][13][14][15].High monounsaturated fatty acids diets also have demonstrated an effect on the secretion of the insulinotropic peptide GLP-1 (glucagon-like peptide 1) [16,17]. GLP-1 is an incretin hormone with antidiabetic action that is capable of stimulating insulin secretion [18,19], increasing beta cell neogenesis [20], inhibiting beta cell apoptosis [20], inhibiting glucagon secretion [21], delaying gastric emptying, and inducing satiety [20,21].…”
mentioning
confidence: 99%
“…Several studies have indicated relationships between the saturation of dietary fat and the concentrations of total plasma cholesterol and higher blood pressure [5], hepatic steatosis [6], adipose chronic inflammation [6], ectopic lipid deposition in the liver and brown fat [6], overweight [6,7], hyperinsulinemia [7], and hepatic insulin resistance [8]. However, high fat diets that are rich in monounsaturated fatty acids exert a protective role [9][10][11][12][13][14][15].…”
mentioning
confidence: 99%
“…EVOO use was also associated with improved post-prandial blood glucose and LDL-C in healthy subjects [8].Habitual consumption of EVOO has been also reported to improve endothelial function in patients with prediabetes and diabetes [9]. Further, the systematic review on beneficial effects of EVOO, and in conjunction with the Mediterranean style diets, reported that EVOO improved inflammation, oxidative stress, coagulation, platelet aggregation, fibrinolysis, and endothelial function [10].In conclusion, although EVOO may have possible antiatherogenic properties, the real beneficial effects of EVOO on human health need to be clarified in new well-designed clinical studies.…”
mentioning
confidence: 99%
“…Habitual consumption of EVOO has been also reported to improve endothelial function in patients with prediabetes and diabetes [9]. Further, the systematic review on beneficial effects of EVOO, and in conjunction with the Mediterranean style diets, reported that EVOO improved inflammation, oxidative stress, coagulation, platelet aggregation, fibrinolysis, and endothelial function [10].…”
mentioning
confidence: 99%
“…). Even though a correct lifestyle that includes proper dietary habits and physical exercise is of preeminent importance(Sherling et al, 2017), accumulated evidence suggests that EVOO and its minor components, via multi-targeted actions, might indeed lower the risk of metabolic syndrome and, after proper randomized trials, might be employed as adjunct therapeutic agents (Yubero-Serrano, Lopez-Moreno,Gomez-Delgado, & Lopez-Miranda, 2018).…”
mentioning
confidence: 99%